(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The theoretical foundations for developing students’ mathematical abilities represent a comprehensive approach that combines psychological, pedagogical and methodological aspects. Mathematical abilities, as one of the key components of cognitive development, are formed under the influence of many factors, including individual personality traits, motivation level, and the quality of the educational environment